Синтез і дослідження властивостей 3-тіосульфонілпохідних 4-(2-метоксифеніл)-5-алкіл(арил)-1,2,4-тріазолу - Кучерявий, Юрій Миколайович; Гоцуля, Андрій Сергійович; Міколасюк, О. О.; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Ачкасова, О. М.; Кучерявый, Ю. Н.; Миколасюк, А. А.; Панасенко, А. И.; Кныш, Е. Г.; Ачкасова, А. Н.; Kucheryavij, Yu. M.; et al. (ЗДМУ, 2014)
Синтез і дослідження властивостей 3-тіосульфонілпохідних 4-(2-метоксифеніл)-5-алкіл(арил)-1,2,4-тріазолу Дослідили реакції отримання 3-тіосульфонілпохідних 4-(2-метоксифеніл)-5-метил1,2,4-тріазолу та 4-(2-метоксифеніл)-5-феніл-1,2,4-тріазолу. Вивчили фізико-хімічні властивості й антимікробну активність синтезованих сполук. Исследованы реакции получения 3-тиосульфонилпроизводных 4-(2-метоксифенил)-5-метил-1,2,4-триазола и 4-(2-метоксифенил)-5-фенил-1,2,4-триазола. Изучены физико-химические свойства и антимикробная активность синтезированных соединений. Synthesis and properties’ investigation of 3-thio sulfonyl derivatives of 4-(2-methoxyphenyl)-5-alkyl(aryl)-1,2,4-triazole The production reactions of 3-thiosulfonyl derivatives of 4-(2-methoxyphenyl)-5-methyl-1,2,4-triazole and 4-(2-methoxyphenyl)5-phenyl-1,2,4-triazole have been investigated. Physical-chemical properties and antimicrobial activity of the synthesized compounds have been studied.
Синтез и исследование свойств 3-тиосульфонилпроизводных 4-(2-метоксифенил)-5-алкил(арил)-1,2,4-триазола
Synthesis and properties’ investigation of 3-thio sulfonyl derivatives of 4-(2-methoxyphenyl)-5-alkyl(aryl)-1,2,4-triazole
Keywords: сульфони; 1,2,4-тріазол; антимікробна активність синтезованих сполук; сульфоны; 1,2,4-триазол; антимикробная активность синтезированных соединений; Sulfones; 1,2,4-triazole; antimicrobial activity